Thermal Performance Evaluation and Its Effect on Visitor Comfort and Exhibits in Museum Bahari Jakarta - Hidayat, Muhammad Syarif; Permata, Suciati (Department of Architecture Universitas Muhammadiyah Jakarta, 2024)
This study evaluates the thermal performance in Museum Bahari, Jakarta, and its impact on visitor comfort and the stability of exhibits. Using both natural ventilation and air conditioning systems, temperature and humidity measurements were taken to assess thermal conditions. The results show that natural ventilation does not meet the standard comfort levels, with average temperatures reaching 29.7°C. Although air-conditioned rooms provided better control, the temperature still exceeded the comfort threshold. Visitor feedback indicated discomfort due to thermal instability. Recommendations include adjusting the opening strategies based on external thermal conditions.